Global South in pursuance of the Global North: case of rural South African education and the Fourth Industrial Revolution - Uleanya, Chinaza; Yassim, Kathija (Comunicação & Educação, 2023)
Nations in the global South tend to embrace ideas, practices, and trends from the global North as the standard. This is in many instances at the expense of their suitability in the current situation and environment of the global South. For instance, issues revolving around the Fourth Industrial Revolution is a typical example. In recent times, the adjustments in the education and other sectors in the Global North to accommodate practices of the Fourth Industrial Revolution are beginning to flood the Global South where many basic and necessary infrastructures are lacking. Issues such as curricular review are being raised and considered, while conferences, workshops, seminars, amongst others are being organized to ensure that learning institutions are positioned to suit the demand of Fourth Industrial Revolution. For instance, coding is fast becoming a major subject to be considered even from primary schools, though not necessarily meeting the local demands.